Pyrazolo[3, 4-d]pyrimidines as sigma-1 receptor ligands for the treatment of pain. Part 1: 4-acylamino derivatives12. Issue 6 (5th May 2017) - Díaz, José Luis; Corbera, Jordi; Cuberes, Rosa; Contijoch, Montserrat; Enrech, Raquel; Yeste, Sandra; Montero, Ana; Dordal, Albert; Monroy, Xavier; Almansa, Carmen
Abstract : The 4-acylaminopyrazolo[3, 4- d ]pyrimidine9a was identified as a highly selective σ1 R antagonist, showing as well substantial antinociceptive properties. Abstract : The synthesis of a new series of 4-acylaminopyrazolo[3, 4- d ]pyrimidines active on the sigma-1 receptor (σ1 R) is reported. Compounds were efficiently prepared using a two to three step process starting from commercially available 1 H -pyrazolo[3, 4- d ]pyrimidin-4-amine. A SAR study shows that the σ1 R requires the presence of relatively highly lipophilic substituents at opposite sides of the central scaffold, while selectivity versus the σ2 R can be improved by shortening the distance of the basic nitrogen to it. Compound9a was among the most active and selective in vitro derivatives and exhibited potent antinociceptive properties in several pain models in mice, indicating its antagonistic behaviour.